Comparative Study on Solar Collectorâs Configuration for an Ejector-Refrigeration Cycle - Senjaya, Raffles; Astina, I Made (ITB Journal Publisher, LPPM ITB, 2008)
Solar collectorâs configuration plays important roleÂ on solar-powered refrigeration systemsÂ to work as heat source for generator . Three types of solar collector consistingÂ of flat plate, evacuated tube, and compound parabolic solar collectorsÂ areÂ comparedÂ toÂ investigateÂ theirÂ performances.Â TheÂ performances consist of the behavior of heat which can be absorbed by the collectors, heat loss fromÂ theÂ collectorsÂ and outlet temperature of working fluid at several slopes of theÂ solarÂ collectors.Â TheÂ newÂ accurateÂ analysisÂ methodÂ ofÂ heatÂ transferÂ is conductedÂ toÂ predictÂ theÂ performanceÂ ofÂ theÂ solarÂ collectors.Â TheÂ analysisÂ is basedÂ onÂ severalÂ assumptions,Â i.e.Â skyÂ conditionÂ atÂ BandungÂ isÂ clearÂ andÂ not raining from 08.00 until 17.00 and thermal resistance at cover and absorber plate isÂ negligible. The numerical calculation results confirm that performance ofÂ the evacuatedÂ tubesÂ solarÂ collectorÂ atÂ theÂ sameÂ operatingÂ conditionsÂ is higherÂ than theÂ others.Â ForÂ theÂ caseÂ ofÂ anÂ evacuated-tubesÂ solarÂ collectorÂ systemÂ with aperture area of 3.5 m2, the maximum heat which can be absorbed is 3992Â W for the highest solar intensityÂ ofÂ 970 W/m2 at 12.00Â withÂ horizontal position ofÂ the solarÂ collector.Â AtÂ thisÂ condition,Â theÂ highestÂ outletÂ temperatureÂ ofÂ waterÂ is 347.15 K with mass flow rate 0.02 kg/s and inlet temperature 298 K.